Análise dos artigos da revista eletrônica investigações em ensino de ciências que apresentem em seu título as palavras “Ensino de Ciências” - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The science teaching is an area of education that has several forms of analysis, can occur directly with students through the performance of activities that seek to evaluate teaching- learning, or only theoretically. Discussing the science teaching in a theoretical method can occur in different ways, being one of these the Scientometry, area of science that provides quantitative reference to the present work. Thus, this research deals with an analysis of articles published in the lectronic journal Investigações em Ensino de Ciências, which focuses on the areas of Chemistry, Physics, Biology. Our study aims to carry out a Quanti-qualitative analysis of the articles published in this journal that have the words "Science teaching" in their title, contributing to a better understanding of the production of this jornal in relation to this specific area. The methodology used was initially characterized in selecting the articles from the description of their title and later the selected articles were classified according to their objectives; areas of education, degree of formation of the first authors, location in which the analyzed research was carried out and geographical distribution of the same. Of a total of 472 publications, 6.35% presented in their title the words science teaching. Resulting in a total number of 30 articles analyzed, of these we emphasize that they had the analysis of periodicals in the area of science teaching as more frequent objectives. The most common area of teaching was the field of natural sciences, worked in an interdisciplinary way and having a greater number of authors with a doctorate degree. Analyzing articles in electronic journals is of fundamental relevance to the academic environment, as it contributes to a broad discussion of the quantity and quality of publications that occur in the area of science teaching, thus subsidizing future discussions in the academic-scientific milieu.
Analysis of the articles of the revista eletrônica investigações em ensino de ciências that present in their title the words “Ensino de Ciências”
Keywords: Educação; Ensino de ciências; Ciências naturais; Cienciometria; Education; Science teaching; Natural sciences; Scientometry; CNPQ::CIENCIAS EXATAS E DA TERRA